A study on the determinants of user acceptance towards electronic payment (e-payment) system among staff of Bank Negara Malaysia / Nurkhairiyyah Ahmad Sukri - Ahmad Sukri, Nurkhairiyyah (Bachelor of Science (Hons) Statistics, 2014)
This research project identifies the determinant of user acceptance towards electronic payment (e-payment) among staff of Bank Negara Malaysia involving the demographic characteristics of respondent and individual perception towards electronic payment system which is Ease of use, Perceived Risk, Trust, Compatibility, External Influence and Facilitating Condition. The electronic payment system is well-known transaction in Bank Negara Malaysia. This study aims to determine the significance different of demographic profile towards acceptance of electronic payment and also to determine the determinants that contribute the User Acceptance of the electronic payments. A total of 400 respondents were randomly selected using Simple Random Sampling. This study collected the data through distributed questionnaires to all selected respondent but only 398 respondents are respond the questionnaire through email and self-administered. The data were analyzed using SPSS 20.0 and Structural Equation Modeling (SEM). The overall findings of this study showed that Education Level is influence the user acceptance toward electronic payment system. While the determinants that contributed the user acceptance towards electronic payment system was facilitating condition. At the end of the study, the several suggestions are proposed to the related parties to solve the identified areas that need to be improved to make the user to accept the use of electronic payment system for various transactions